SOCIAL-PEDAGOGICAL WORK IN UKRAINE: HISTORY, EXPERIENCE, PERSPECTIVES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with the issues of the formation and development of social pedagogy in the field of social work and the perspectives for its further development, because in the today's conditions, in accordance with the priority vectors of the state social policy, social-pedagogical work with various social groups is significantly intensified. The purpose of the article is to analyze the development of socio-pedagogical work in Ukraine and offer vectors of its perspectives.An analysis of theoretical and methodological approaches to the characteristics of such paradigms of social and pedagogical activity as cognitive-informational, competence, personal, and culturological ones is proposed. The legal and regulatory framework of social-pedagogical work in Ukraine is analyzed. The most effective mechanisms of social and pedagogical work at different stages of its development are singled out. Considerable attention is paid to the practical activities of a social educator in the educational environment. An attention is also paid to inclusive education in accordance with the provisions of the Law of Ukraine ‘On Education'. The description of the content, forms and methods of social pedagogical practice according to the challenges of the time is given.The prospective directions of modernization of social and pedagogical work are proposed to introduce the educational institutions of higher education of innovative specialization in the specialty ‘Social pedagogy', namely, socio-pedagogical patronage in inclusive education, the coordinator of social and pedagogical work, the assistant of a social pedagogue, teacher-organizer, social management pedagogical work, social- pedagogical counseling, social-pedagogical counseling of volunteers in the social sphere, etc. Of course, these proposals are controversial.
Keywords: socio-pedagogical work, social pedagogy, socialization, educational environment, livelihoods, theoretical approaches, paradigm, inclusive education.